THE UNITED NATIONS FRAMEWORK CONVENTION ON INTERNATIONAL TAX COOPERATION IN THE MAKING. DEBATE AND APPROVAL OF ITS TERMS OF REFERENCE - Grau Ruiz, María Amparo (Crónica Tributaria)
This contribution analyzes the process currently underway to establish a United Nations Framework Convention on International Tax Cooperation. It reviews the recent debate in the Ad Hoc Committee to approve its terms of reference and the treatment finally given to the most urgent issues in the matter by the UN General Assembly by including them in the Compact for the Future.